STUDI PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS INTEGRASI ISLAM – SAINS PADA POKOK BAHASAN SISTEM REPRODUKSI KELAS IX MADRASAH TSANAWIYAH - Faiz Hamzah (Universitas Muhammadiyah Sidoarjo, 2015)
Develop integrative learning materials between Islam and Science in the science subjects is an attempt to bring science-based values in an effort to improve and raise the awareness of students on the aspects of intellectual, emotional and spiritual. This is done so that the impression of general subjects that have not contributed to moral and character education to increase faith and piety learners are not proven. Therefore, using the model of Dick and Lou Carey in the design of scientific development, integrative Islam and Science approach philosophical dimension as a foundation and Integration dyadic Dialogic, this study was conducted to address issues of common subjects who did not leave sumabngsih to the formation of character and morality